Reanalysis of sequences of alleged Javan tiger highlights the difficulties in studying big cats and the need for high-throughput sequencing - Anubhab Khan; Yulianto Yulianto; Sabhrina Gita Aninta; Wirdateti Wirdateti (Oryx)
Big cats are of conservation concern throughout their range, and genetic tools are often employed to study them for various purposes. However, there are several difficulties in using genetic tools for big cat conservation that could be resolved by modern methods of DNA sequencing. Recent reports of the sighting of a putative Javan tiger Panthera tigris sondaica in West Java, Indonesia, highlight some of the difficulties of studying the genetics of big cats. We reanalysed the data of the original reports and found that the conclusions were drawn based on incorrect copies of the genes. Specifically, the nuclear copy of the mitochondrial gene was analysed with the mitochondrial sequence, leading to discordance in the results. However, re-sequencing of the remaining DNA confirms that the sighting could have been that of a tiger, but the subspecies cannot be confirmed. This work highlights the urgency of developing high-throughput sequencing infrastructure in the tropics and the need for reliable databases for the study of big cats.